Evolution Of Sape: From Longhouse To The International Stage - Lim, Connie Keh Nie; Mohd. Fadzil, Abdul Rahman (Institute of Borneo Studies, UNIMAS, 2016)
Sape, a boat lute shape, plucked stringed musical instrument played among the Kayan and Kenyah people in Central Borneo and the Dayak in Kalimantan Indonesia. This musical instrument is often used as the symbol in promoting Malaysia in the areas of arts, culture and tourism. It is also the symbol of the state of Sarawak. In Sarawak, sape is the traditional instrument of the Kenyah, Kayan, Kelabit, Penan and other ethnic tribes of Orang Ulu community living in Kapit, Bintulu, Miri, Limbang district. Over the past 40 years, the instrument is brought to travel and perform in different parts of the world by different sape players. This shows that the sape music which is traditionally played to accompany dances during festivals and as a form of entertainment in the longhouses and villages is now performing at musical festivals such as the arts, cultural and tourism promotions in various countries. Hence, this paper aims to trace the development of sape in terms of its physical structure and the evolution of sape from the perspective of its performance practice and repertoire.